2018
DOI: 10.1101/420620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Notch2 signaling regulates Id4 and cell cycle genes to maintain neural stem cell quiescence in the adult hippocampus

Abstract: Neural stem cells (NSCs) in the adult hippocampal dentate gyrus (DG) can be quiescent or proliferative, but how they are maintained is largely unknown. With age DG NSCs become increasingly dormant, which impinges on neuron generation. We addressed how NSC activity is controlled and found that Notch2 promotes quiescence by regulating their transition to the activated state. Notch2-ablation induces cell cycle genes and markers of active NSCs.Conversely, quiescent NSC-associated genes, including Id4, are down reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 54 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…In this line, in adult hippocampal NSCs it has been reported that, in order to return to the quiescent state, the pro-activation transcription factor ASCL1 is destabilized by the E3-ubiquitin ligase Huwe1 (Urbán et al, 2016). The degradation of ASCL1 is further promoted by Id4 expressed in quiescent radial glia-like NSCs (Blomfield et al, 2019;Zhang et al, 2019), while in muscle stem cells MyoD is transcribed during quiescence yet its translation is inhibited by an RNA-binding protein (de Morrée et al, 2017). A common emerging theme, therefore, is that transcription factors involved in shaping the transcriptional landscape of active and quiescent adult stem cells require fine post-transcriptional regulation to fulfill their function.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this line, in adult hippocampal NSCs it has been reported that, in order to return to the quiescent state, the pro-activation transcription factor ASCL1 is destabilized by the E3-ubiquitin ligase Huwe1 (Urbán et al, 2016). The degradation of ASCL1 is further promoted by Id4 expressed in quiescent radial glia-like NSCs (Blomfield et al, 2019;Zhang et al, 2019), while in muscle stem cells MyoD is transcribed during quiescence yet its translation is inhibited by an RNA-binding protein (de Morrée et al, 2017). A common emerging theme, therefore, is that transcription factors involved in shaping the transcriptional landscape of active and quiescent adult stem cells require fine post-transcriptional regulation to fulfill their function.…”
Section: Discussionmentioning
confidence: 98%
“…The same comparison with genes that were putatively regulated by A-specific or PAN enhancers was not significant (p > 0.05, Chi-squared test). Among these 406 upregulated genes, we encountered genes expressed by hippocampal dentate gyrus precursors throughout embryonic and postnatal development (Hopx) (Berg et al, 2019), as well as genes enriched in quiescent adult radial-glia like NSCs (Id4) (Blomfield et al, 2019;Zhang et al, 2019). Out of the 406 genes, 126 showed the LEF1 motif exclusively in the Q enhancers (this is, they lacked the motif in the PAN and A enhancers, Supplementary Table S3; note that 115 out of the 126 genes had both LEF1 and NFIX motifs at one or more Q-specific enhancers).…”
Section: Lef1 Binding Motifs Enriched In Nspc Enhancers and Putative ...mentioning
confidence: 99%
“…However, downstream targets of the Notch pathway (Hes and Hey transcription factors) are only expressed by NSCs. This indicates that Notch signaling in the neurogenic niches is highly regulated and not only due to receptor or ligand expression by a cell (Figure 2A; Stump et al, 2002;Irvin et al, 2004;Nyfeler et al, 2005;Carlen et al, 2009;Aguirre et al, 2010;Lugert et al, 2010;Basak et al, 2012;Kawaguchi et al, 2013;Lavado and Oliver, 2014;Ehret et al, 2015;Kawai et al, 2017;Semerci et al, 2017;Engler et al, 2018a,b;Zhang et al, 2018;Sueda et al, 2019;Zhang et al, 2019;Harada et al, 2021). Notch signaling can be regulated at multiple levels modulating the strength and dynamics of the signal outcome.…”
Section: Notch Signaling In Adult Neurogenesismentioning
confidence: 96%
“…Expression of all four Notch receptor paralogs has been documented in various cell types of the adult mouse brain including by NSCs (Notch1, Notch2 and Notch3), astrocytes (Notch1 and Notch2), neurons (Notch1 and Notch2), endothelial cells (Notch1 and Notch4) and vascular smooth muscle cells and pericytes (Notch3) (Basak et al, 2012;Ehret et al, 2015;Llorens-Bobadilla et al, 2015;Shin et al, 2015;Kawai et al, 2017;Rieskamp et al, 2018;Engler et al, 2018a;Zhang et al, 2019;Ho et al, 2020). Furthermore, Notch receptors and many of their ligands are expressed by NSCs, progenitors and neuroblasts throughout the adult neurogenic lineage.…”
Section: Notch Signaling In Adult Neurogenesismentioning
confidence: 99%
“…In the Notch2 conditional KO, Id4 expression was significantly reduced, while forced Id4 expression induced differentiation towards the astrocyte lineage. Thus, Notch2 acts to maintain quiescence and includes Id4 as the main downstream regulator together with Hes1/Hes5 expression induction, which then represses the pro-neural TF Ascl1 and maintains NSCs in the dormant state (Zhang et al, 2019).…”
Section: Early Events: From Stemness and Proliferation To Cell Fate D...mentioning
confidence: 99%